Effect of Drill Passing Down With Walls and Pairs Against Accuracy of Underpass in Volleyball Game - Ilhamdi Ilhamdi; Ade Rahmat; Zusyah Porja Daryanto (INSPIREE: Indonesian Sport Innovation Review, 2023)
The purpose of the study. This study aims to determine the difference in the effect of paired bottom passing exercises and bottom passing exercises reflected against the wall on the level of lower passing ability of MTSs YPPU Karimunting men's volleyball extracurricular participants, Bengkayang Regency. Materials and methods. The design of this study is a two group pretest-post test design. The sample of this study was students participating in extracurricular men's volleyball MTSs YPPU Karimunting with a total of 30 students. The instrument used in this study was the bottom passing ability test. Data analysis techniques use t-tests through normality tests, homogeneity tests, and hypothesis tests. Results. The results showed: (1) There was a significant effect of paired bottom passing training on the level of lower passing ability of MTSs YPPU Karimunting men's volleyball extracurricular participants, it can be seen that t count is 2.131 > t table (1.746), while p value (0.000) < 0.05. (2) There is a significant effect of lower passing training reflected against the wall on the level of lower passing ability of MTSs YPPU Karimunting men's volleyball extracurricular participants, it can be seen that the results of the t test obtained t count of 2.160 > t table (1.771), while the p value (0.000) < 0.05. Conclusions. These results mean that there is a significant effect of pair-bottom passing training on the level of lower passing ability of men's volleyball extracurricular participants at MTSs YPPU Karimunting, Sungai Raya Kepulauan sub-district, Bengkayang district.